2018
DOI: 10.1002/ijc.31808
|View full text |Cite
|
Sign up to set email alerts
|

NAMPT signaling is critical for the proangiogenic activity of tumor‐associated neutrophils

Abstract: Tumor-associated neutrophils (TANs) regulate many processes associated with tumor progression, and depending on the microenvironment, they can exhibit pro- or antitumor functions. However, the molecular mechanisms regulating their tumorigenicity are not clear. Using transplantable tumor models, we showed here that nicotinamide phosphoribosyltransferase (NAMPT), a molecule involved in CSF3R downstream signaling, is essential for tumorigenic conversion of TANs and their pro-angiogenic switch. As a result tumor v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 44 publications
3
70
0
1
Order By: Relevance
“…NAMPT has also been shown to be upregulated in tumor associated neutrophils (TANs) in patients with melanoma and head and neck cancer, and in murine cancer models. Inhibition of NAMPT in ex vivo TANs followed by adoptive transfer of the TANs into tumor-bearing mice reduced tumor angiogenesis and proliferation through suppression of SIRT1 and resultant transcriptional blockade of proangiogenic genes (143). While more studies are required to better understand the role NAMPT inhibition plays in the microenvironmental immune milieu, these and other preliminary reports suggest NAMPT inhibitors could be used to enhance immunotherapies in the clinic (144).…”
Section: Immune Regulation Of Tumor Microenvironmentmentioning
confidence: 98%
“…NAMPT has also been shown to be upregulated in tumor associated neutrophils (TANs) in patients with melanoma and head and neck cancer, and in murine cancer models. Inhibition of NAMPT in ex vivo TANs followed by adoptive transfer of the TANs into tumor-bearing mice reduced tumor angiogenesis and proliferation through suppression of SIRT1 and resultant transcriptional blockade of proangiogenic genes (143). While more studies are required to better understand the role NAMPT inhibition plays in the microenvironmental immune milieu, these and other preliminary reports suggest NAMPT inhibitors could be used to enhance immunotherapies in the clinic (144).…”
Section: Immune Regulation Of Tumor Microenvironmentmentioning
confidence: 98%
“…It is also not clear if N2 cells can change into N1 cells and vice versa under the influence of changes in the tumor microenvironment [9]. An interesting study in that regard recently described how nicotinamide phosphoribosyltransferase (NAMPT)part of the G-CSF signaling cascademight be involved in the protumorigenic conversion of neutrophils inside the tumor microenvironment by affecting angiogenesis [128]. In this study, inhibition of NAMPT signaling was shown to decrease the expression of the proangiogenic factors matrix metalloproteinase 9 (MMP-9), VEGF, and S100 calcium-binding protein A8 (S100A8) in TANs relative to control treatment, thus impairing the development of a functional tumor vasculature [128].…”
Section: Micementioning
confidence: 99%
“…An interesting study in that regard recently described how nicotinamide phosphoribosyltransferase (NAMPT)part of the G-CSF signaling cascademight be involved in the protumorigenic conversion of neutrophils inside the tumor microenvironment by affecting angiogenesis [128]. In this study, inhibition of NAMPT signaling was shown to decrease the expression of the proangiogenic factors matrix metalloproteinase 9 (MMP-9), VEGF, and S100 calcium-binding protein A8 (S100A8) in TANs relative to control treatment, thus impairing the development of a functional tumor vasculature [128]. Moreover, recent work suggested that a glucose-restricted tumor microenvironment could induce metabolically adapted, oxidative neutrophils, and maintain intratumoral immunosuppression by a subpopulation of TANs [129].…”
Section: Micementioning
confidence: 99%
“…Mantovani et al (20) showed that tumor-associated inflammation is characterized by the swelling of inflammatory cells and the production and release of inflammatory factors in tumor tissues. Inflammatory cells and immune cells, such as neutrophils, lymphocytes, and monocytes, in the peripheral blood of patients with tumor-associated inflammation are considered to be important factors leading to tumor development, invasion and metastasis (21)(22)(23)(24). Existing studies have shown that the NLR and LMR play important roles in determining the prognosis of cancer patients (25-27).…”
Section: Discussionmentioning
confidence: 99%